Mixing knowledge to negotiate with and on a volcano - Jean-Baptiste Bing (Revue de Géographie Alpine)
The Javanese world is organized in the form of hierarchical concentric circles, with one of its limits being in the mountains. This particular limit is the realm of the supra-human (gods, spirits) as much as the infra-human (animals and wild plants) and should be approached with caution, through continual negotiation with the forces that inhabit the area. This holistic view of humankind’s place in the world is increasingly contested, however, by a movement that has been powerful in Indonesia for some thirty years, mixing Islamisation and modernization. The process has modified the notion of border between human and non-human, not only from a symbolic and intellectual point of view but also in terms of spatial practices. A mix of knowledge and know-how seems to dominate all segments of the population, and confrontation between these types of knowledge is causing some very concrete problems concerning, for example, management and control of territories, and access to local resources, but is also leading to a renewal of territoriality linked to the margins of the ecumene, which are the forest and the volcano’s crater.